An investigation of the assembly of transistor cores: first year project 1964/65 - College of Aeronautics, (Cranfield) (College of Aeronautics, 1965)
1. Introduction This project was carried out for the Texas Instrument Company of Bedford/ by members of the Ergonomics/ Operational Research and Management sections at Cranfield. Texas Instruments wanted to increase production of doUble alloy transistors by 25%. The increase could not be achieved by hiring extra operators because the amount of floor space was limited. The problem facing the group therefore was one of expanding output by increasing the efficiency and productivity of the existing operators ... [cont.].